2023
DOI: 10.3390/nu15122754
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Interactions between Zinc and Vitamin A on Intestinal Functionality, Morphology, and the Microbiome In Vivo (Gallus gallus)

Abstract: Dietary deficiencies in zinc (Zn) and vitamin A (VA) are among the leading micronutrient deficiencies globally and previous research has proposed a notable interaction between Zn and VA physiological status. This study aimed to assess the effects of zinc and vitamin A (isolated and combined) on intestinal functionality and morphology, and the gut microbiome (Gallus gallus). The study included nine treatment groups (n~11)—no-injection (NI); H2O; 0.5% oil; normal zinc (40 mg/kg ZnSO4) (ZN); low zinc (20 mg/kg) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In this study, the potential effects of soluble extracts from the cotyledon and seed coats of different pea varieties on the expression of brush border membrane iron-related proteins (DCTYB and DMT-1) and populations of beneficial intestinal bacteria was assessed using the Gallus gallus model. The Gallus gallus model in previous studies has been proven to be valid for initial in vivo screening of iron bioavailability in staple foods due to its sensitivity to micronutrient deficiency, taxonomic similarities at the phylum level between humans and this model, as well as genetic similarities in nutrient metabolism proteins between the two [ 34 , 41 , 48 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the potential effects of soluble extracts from the cotyledon and seed coats of different pea varieties on the expression of brush border membrane iron-related proteins (DCTYB and DMT-1) and populations of beneficial intestinal bacteria was assessed using the Gallus gallus model. The Gallus gallus model in previous studies has been proven to be valid for initial in vivo screening of iron bioavailability in staple foods due to its sensitivity to micronutrient deficiency, taxonomic similarities at the phylum level between humans and this model, as well as genetic similarities in nutrient metabolism proteins between the two [ 34 , 41 , 48 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the body lacks an active iron excretion system, iron homeostasis is tightly regulated to maintain iron balance, and this is predominantly controlled at the level of iron absorption from the intestines [ 81 , 85 ]. Thus, in a state of iron deficiency, more iron is mobilized from body iron stores and increased intestinal iron absorption [ 50 ]. These processes are, however, downregulated when the body is iron-replete [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc, an indispensable trace element, plays a pivotal role in numerous enzymatic reactions, immune modulation, and the process of wound healing [198]. Studies in humans and chickens, as well as ex vivo research using cultures of spleen leukocytes from dogs, have suggested the existence of a synergistic relationship between the dietary intake of zinc and the metabolism and status of vitamin A [199][200][201]. Simultaneous long-term zinc and vitamin A supplementation was shown to be associated with reduced parasitic gastrointestinal infections caused by Giardia lamblia and Ascaris lumbricoides in humans [202].…”
Section: Vitamin a And Zincmentioning
confidence: 99%
“…Moreover, zinc deficiency has been shown to diminish the lymphatic absorption of retinol in animal models, a phenomenon linked to a decline in the output of lymphatic phospholipids due to compromised biliary secretion into the intestinal lumen [205]. Conversely, vitamin A is required for the absorption and utilization of zinc by improving intestinal functionality [201,204].…”
Section: Vitamin a And Zincmentioning
confidence: 99%